Database Management using Embedded System and CAD - Mary M, Anitha; R, Bharathy; Shree U, Jhanani; Jebasingh S, Richard (International Journal of Engineering and Technology, 2018)
An aim of this paper is to use Radio Frequency Identification (RFID) technology in facilitating efficient file management system. RFID is an abbreviation of radio frequency identification, RFID was poised to take off and become a standard piece of library technology. An RFID transmitter is also needed to capture the radio frequency signal from the tag for turn out to be giving out by the RFID reader. Therefore RFID has been referred to as â€œa non-contact method of using radio frequency electromagnetic waves for communication between two remote entitiesâ€. An Objective of this paper is to design 3D modeling of file rack using Creo software, manage the files using RFID tag, read the files from RFID using microcontroller through embedded code and to display the files using 16x2 Liquid Crystal Display and 4x4 keypad. The position of the files in the rack will be identified using Light Emitting Diode.Â Â